Statistical profiles of female juvenile homicide offenders: a latent class analysis - Cochran, John K. (The Routledge international handbook of juvenile homicide, 2024)
The limited research on female juvenile homicide offenders (JHOs) has used largely small clinical samples, and to date, there have been no empirically driven typologies of female JHOs using nationwide samples of offenders. In order to address this gap in the literature, we used a national sample of 3887 female juvenile murderers obtained from 41 years of data in the FBI’s Supplementary Homicide Report (SHR) to develop the first statistical typology of female JHOs in the United States. Using key characteristics of the offenders (race, age, use of accomplices), victims (sex, race, age), and the homicide incident (victim-offender relationship, weapon used, homicide circumstances) as grouping covariates, we conducted a latent class analysis (LCA) to identify statistical subtypes of female juvenile-perpetrated murders. Based on goodness-of-fit indicators, we detected nine unique classes of female JHOs. We discuss these unique classes and compare them to six distinct classes we identified in an LCA of over 44,000 male JHOs. Our comparative analysis revealed four overlapping themes between male and female JHOs. However, there was one subtype that was unique to female JHOs: the killing of intimate partners. This heterogeneity among female JHO cases may be critical from an investigative standpoint when linking specific victim and homicide incident characteristics to specific offender characteristics. Additional practical and theoretical implications are discussed.